Math, asked by nayabkhan80728, 6 months ago

answer fast please I will mark you as brainlist​

Attachments:

Answers

Answered by dddivyanshu5552
0

Answer:

( \times  - 3) \div 5 - 2 = 2 \times  \div 5 \\ ( \times  - 3) \div 5 = 2 \times  \div 5 + 2 \\ then \: taking \: 5as \: common \: we \: will \: remove \: 5 \:  \\ so \: now \:  \times  - 3 =  2 \times  + 2 \\   - 3 - 2 = 2 \times  -  \times  \\  \times  =  - 5

pls mark it as brainliest

Answered by maitri1006
0

Answer:

Apko ye dehkkar pata chal jayega please mark brainliest :( it is needed

Attachments:
Similar questions